2009
DOI: 10.1177/0969733009106650
|View full text |Cite
|
Sign up to set email alerts
|

Licensed Nurses’ Perceptions of Ethical Climates in Skilled Nursing Facilities

Abstract: This study examines the presence of ethical climates in skilled nursing facilities and identifies their antecedents (work group, job position, tenure). A cross-sectional survey design was implemented. A total of 359 facilities were selected in the Midwestern United States. Responses were received from nurses representing 100 of those facilities (28%). A total of 656 usable questionnaires were returned of the 3060 distributed (21.4% response rate). Descriptive statistics, confirmatory factor analysis, and multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
57
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(69 citation statements)
references
References 35 publications
9
57
0
1
Order By: Relevance
“…Moreover, developing benevolent and principled ECs may help to reduce moral stress for nurses, improve moral excellence, and enhance the organization's success not only in retaining and recruiting new nurses but also in increasing employee productivity through ethical behavior. 9 This goes in the same line with the finding of this study which revealed positive significant correlations between nurses' perception of overall ethical work climate and their perception of each of POS, OC, as well as their JS. A positive relationship also was found between each variable with another.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Moreover, developing benevolent and principled ECs may help to reduce moral stress for nurses, improve moral excellence, and enhance the organization's success not only in retaining and recruiting new nurses but also in increasing employee productivity through ethical behavior. 9 This goes in the same line with the finding of this study which revealed positive significant correlations between nurses' perception of overall ethical work climate and their perception of each of POS, OC, as well as their JS. A positive relationship also was found between each variable with another.…”
Section: Discussionsupporting
confidence: 86%
“…2 Acquiring knowledge about the effect of ethical work climate and level of POS and factors amenable for change in the work environment can help organizational leaders to deal effectively within dysfunctional behaviors and make a difference in enhancing nurses' dedication and loyalty to their organization. 9,12 Conceptual framework This study was guided by the conceptual framework developed by Filipova 12 which proposed the relationship between certain organizational variables (i.e. ethical work climate and POS) and other mediating variables (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Shared understanding of what is ethically correct action and how ethical problems should be handled usually reflect the ethics of the particular organisation. 4 Based on results, competence in ethical decision-making was estimated to be the lowest but still at average level among nurses. According to Goethals et al, 18 'various studies, however, indicated that a gap exists between the ideal ethical decision and the real ethical action'.…”
Section: Discussionmentioning
confidence: 99%
“…For sensitive issues regarding "patient care", nurse managers felt "discuss with doctors" was the best option probably as the immediate reliable measure for dealing with the issues. Filipova AA's study (2009) suggested that the way ethical issues are handled reflects the ethics of an organization [19]. Hence, this result implies that the working environment between doctors and nurse managers are still at best situation in the hospitals.…”
Section: Discussionmentioning
confidence: 99%